Pendampingan Pembelajaran Bahasa Inggris Berbasis Kendala Linguistik Bahasa Daerah Bagi MGMP Bahasa Inggris SMK Kabupaten Lombok Barat - Arafiq; Arifuddin; Atri Dewi Aziz; Mh. Isnaini (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This community service aims to provide training of learning English based on linguistic constraints of regional languages to members of MGMP (Discussion Forum for English teacher) of Vocational High School of West Lombok. This service is relevant to sociocultural problems that the English teachers of the schools, especially vocational schools of West Lombok Regency. The problems the teachers are facing are (1) the influence of regional languages ​​still causes a decline in interest in learning English, (2) students are not yet aware of the influence of regional languages ​​spoken in English language practices, and (3) teachers have not found the right way to make students aware of the influence of their regional languages ​​in English lessons. This service was carried out through participatory method expecting direct participation of during the processes and stages from planning, implementation, and evaluation. Regarding the types of problems mentioned above, the services offered are as follows: (1) providing counseling to teachers about the types of influence of regional languages ​​spoken by students (regional languages ​​in NTB) on learning English subjects, (2) providing guidance to teachers on how to build student awareness so that they can anticipate the influence of regional languages ​​in learning English subjects, and (3) providing guidance on how to integrate learning based on linguistic constraints of regional languages ​​into English subject learning activities. The output expected from this Community Service are (1) the publication of a publication article in national proceedings and (2) a statement on the use of technology for implementing learning based on linguistic constraints of regional languages ​​in English language learning in vocational schools throughout West Lombok Regency, West Nusa Tenggara.